Analysis Of Factors Affecting The Effectiveness Of Handling Over-Dimension And Overloading (Odol) In East Java At Uppkb Trosobo Sidoarjo And Uppkb Singosari Malang - I Made Buda Atmajaya; Haris Muhammadun; Wateno Oetomo (Al-Makki Publisher, 2023)
The problem of Overdimension and Overloading (ODOL) freight transportation has become a national issue. Various impacts caused by ODOL freight transportation include a decrease in vehicle speed, a decrease in road technical life, loss of road maintenance budget, vehicle damage, and the occurrence of traffic accidents on the road. East Java Province has a fairly high economic activity by using freight transportation in various conditions including Overdimension and Overloading. The Ministry of Transportation through the UPPKB Service Unit throughout East Java has made various efforts to handle ODOL freight transportation, but the level of violations of freight transportation still occurs. This study aims to determine the factors that affect the effectiveness of handling Overdimension and Overloading (ODOL) in freight transportation so that it can provide recommendations for appropriate ODOL handling. The data collection method used interviews and questionnaires to Korsatpel, UPPKB Operational Staff, and freight transport drivers. While the analysis method used fishbone diagram analysis and multiple linear regression analysis using field data. Based on the results of the study, it is known that the dominant factors that affect the effectiveness of handling Overdimension and Overloading (ODOL) in freight transportation are the enforcement of Tilang (X1) and Transfer of Cargo / Transfer of Excess Load (X3) with the value of coefficient determination at UPPKB Trosobo and Singosari of 96.1% and 92.3%. The handling recommendations given are the need to increase ticket fines and provide transportation services for excess cargo in the form of vehicles and transportation personnel as well as forklifts and cranes at the UPPKB Satpel to move heavy loads.